Motivational factors in makerspaces: a mixed methods study of elementary school students' situational interest, self-efficacy, and achievement emotions - Vanessa W. Vongkulluksn; Ananya M. Matewos; Gale M. Sinatra; Julie A. Marsh (SpringerOpen, 2018)
Abstract Background Design-based learning and makerspace programs have been shown to be effective in increasing student motivation for STEM learning. Since these programs have largely been implemented for middle school and older students, less is known about their motivational implications in elementary school contexts. The purpose of this study was to understand how elementary school students' (grades 3-6) self-efficacy changed throughout the semester of a design-based makerspace course, and how these changes are associated with experiences of positive and negative achievement emotions. Additionally, this study investigated how self-efficacy and achievement emotions are related to students' interest development in the makerspace course. Results Results of hierarchical growth modeling showed that although students' self-efficacy and situational interest remained moderately high during the course, both declined over the makerspace semester. Further, self-efficacy, as well as experiences of excitement and frustration with project tasks were found to be associated with students' situational interest. Interpretive analysis of student think-aloud interviews and classroom observations supported these findings. Conclusions Design-based makerspaces have the potential to trigger elementary school students' interest in STEM activities. However, the iterative design process can lead to suboptimal outcomes on students' self-efficacy and interest. Instructors should offer context-sensitive efficacy- and emotion-related scaffolds to foster positive makerspace experiences.